Self-reported sense of purpose in life and proxy-reported behavioral and psychological symptoms of dementia in the last year of life. (14th July 2022) - Sutin, Angelina R.; Luchetti, Martina; Stephan, Yannick; Terracciano, Antonio
Abstract: Objectives: Behavioral and psychological symptoms of dementia (BPSD) are among the most challenging aspects of dementia for individuals living with dementia and their caregivers. Identifying factors associated with resilience to BPSD may inform interventions to reduce them. The present research examines whether purpose in life is associated with BPSD in the last year of life. Method: Participants from the Health and Retirement Study were selected if they reported on their sense of purpose, had evidence of a memory impairment, died across the follow-up, and a proxy completed the End of Life survey that included BPSD ( N  = 2473). Self-reported sense of purpose was tested as a predictor of the sum of symptoms and each indivdual symptom in the last year of life. Results: Purpose in life was associated with fewer BPSD overall. Of the individual symptoms, purpose was associated with less risk of psychological symptoms, specfiically less depression, periodic confusion, uncontrolled temper, but not with motor or perceptual symptoms. Conclusion:  These results are consistent with growing evidence that purpose is associated with better cognitive outcomes. Purpose may be a useful target of intervention to improve outcomes across the spectrum of dementia